Numerical exploration of radiative heat transfers in a magneto bioconvection Maxwell fluid passing through a spinning disk - Ebrahem A Algehyne; Fahad Maqbul Alamrani; Showkat Ahmad Lone; Farhan Ali; Anwar Saeed; Arshad Khan (Advances in Mechanical Engineering, 2024)
When applied to a rotating disk, Maxwell nanofluids have a wide range of applications in various fields. They provide increased heat transfer efficiency in cooling systems, which is essential for preserving the ideal operating temperatures of spinning gears like disk brakes and turbines. Furthermore, Maxwell nanofluids in microfluidic devices provide improved fluid manipulation and control, improving performance in applications such as microscale pumps and lab-on-a-chip systems. This article has numerically examined the magneto-bio-convection flow of Maxwell, which includes nanofluid, past a disk surface based on these applications. We present the model equations in PDE format, then shift them to ODEs using the appropriate variables. We utilize the bvp4c approach to obtain numerical solutions to the modeled equations. We also take into account the effects of thermal radiation, heat sources, Brownian motion, thermophoresis, chemical reactivity, and activation energy. We find that a higher stretching/shrinking variable has enhanced the radial velocity profile, while simultaneously diminishing the axial and angular velocity field. While the velocity profiles in the axial direction and redial direction have reduced with larger magnitude of Maxwell fluid variable. The thermal distributions have risen due to higher magnetic, Brownian motion, thermophoresis, heat sources, and thermal radiation components. Thermophoresis, magnetic and thermal radiation, heat sources, and Brownian motion all contribute to an increase in heat transfer rates.